2009
DOI: 10.1021/jf803755s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vitamin B12 Compounds from Korean Purple Laver (Porphyra sp.) Products

Abstract: Vitamin B(12) contents of various Korean purple laver products were determined with the microbiological vitamin B(12) assay method. Although a substantial amount (133.8 microg/100 g) of vitamin B(12) was found in dried purple laver, seasoned and toasted laver products contained lesser vitamin B(12) contents (about 51.7 microg/100 g). The decreased vitamin B(12) contents in the seasoned and toasted laver products, however, were not due to loss or destruction of vitamin B(12) during the toasting process. Silica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…A substantial amount (133.8 μg/100 g dry weight) of Vitamin B 12 was found in dried Korean purple laver ( Porphyra sp. ), but seasoned and toasted laver products contain lower amounts of Vitamin B 12 (approximately 51.7 μg/100 g dry weight) [57]. In particular, when the dried purple laver was treated by toasting until the laver’s color changed from purple to green, the decreases in the Vitamin B 12 contents of the seasoned and toasted laver products were not due to the loss or destruction of Vitamin B 12 during the toasting process [57].…”
Section: Vitamin B12-containing Plant-derived Food Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…A substantial amount (133.8 μg/100 g dry weight) of Vitamin B 12 was found in dried Korean purple laver ( Porphyra sp. ), but seasoned and toasted laver products contain lower amounts of Vitamin B 12 (approximately 51.7 μg/100 g dry weight) [57]. In particular, when the dried purple laver was treated by toasting until the laver’s color changed from purple to green, the decreases in the Vitamin B 12 contents of the seasoned and toasted laver products were not due to the loss or destruction of Vitamin B 12 during the toasting process [57].…”
Section: Vitamin B12-containing Plant-derived Food Sourcesmentioning
confidence: 99%
“…), but seasoned and toasted laver products contain lower amounts of Vitamin B 12 (approximately 51.7 μg/100 g dry weight) [57]. In particular, when the dried purple laver was treated by toasting until the laver’s color changed from purple to green, the decreases in the Vitamin B 12 contents of the seasoned and toasted laver products were not due to the loss or destruction of Vitamin B 12 during the toasting process [57]. In vitro gastrointestinal digestion experiments indicated that the estimated digestion rate of Vitamin B 12 from dried purple laver was approximately 50% at pH 2.0 (as a model of normal gastric function).…”
Section: Vitamin B12-containing Plant-derived Food Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not estimate the digestion rate of the phycoerythrobilin compound due to difficulty in assaying the compound in the dried laver. Using the same digestion method, Miyamoto et al (2009) estimated the digestion rate of vitamin B 12 in the Korean purple laver to be about 50%.…”
Section: Methodsmentioning
confidence: 99%
“…As summarized by Skrov á nkov á (2011), algae are relevant sources of vitamin B 12 , with Porphyra sp. presenting the highest content: 133.8 mg B 12 /100 g dry matter (Miyamoto et al , 2009). Others reported B 12 content of this algae in the range 12.0-68.8 mg/100 g dry matter (Watanabe et al , 2002(Watanabe et al , , 2007.…”
Section: Vitaminsmentioning
confidence: 98%